Deteksi Dini Karies Gigi sebagai Upaya Pencegahan Penyakit Gigi dan Mulut pada Siswa Diaspora di Sekolah Indonesia Jeddah dan Mekkah, Arab Saudi - Hayyu Failasufa; Nur Khamilatusy Sholekhah; Megawati Prajarini; Risyandi Anwar; Ika Rachmawati; Gelar Subhakti Ramdhani; Putri Dhianita Pratiwi; Muhammad Destyatosa Irfani (Jurnal Pengabdian UNDIKMA, 2026)
This community service activity aims to conduct early detection of oral health problems through simple preliminary examinations using clinical instruments, while improving students’ knowledge through oral health education as an effort to prevent dental and oral diseases. The program involved 110 students from the Indonesian Schools in Jeddah and Mecca. The activity was implemented using a health empowerment approach, with dental and oral examinations conducted using the Oral Health Surveys: Basic Methods issued by the World Health Organization (WHO). The collected data were analyzed based on frequencies and percentages. The screening results showed a high prevalence of dental caries, with 51.8% of students having a DMF-T score > 0. The 10–12-year age group accounted for the highest proportion of caries cases at 73.6%. The most commonly required treatment recommendation was dental fillings, representing 38.2% of cases. The high prevalence of caries among diaspora students highlights the importance of sustainable early detection programs and oral health education. This intervention is expected to foster good oral hygiene habits from an early age in order to prevent more severe dental diseases in the future.